CD146‐mediated acquisition of stemness phenotype enhances tumour invasion and metastasis after EGFR‐TKI resistance in lung cancer. (27th January 2019) - Zhang, Fan; Wang, Jia; Wang, Xiaobo; Wei, Nan; Liu, Haiyang; Zhang, Xiaoju
Abstract: Introduction: Tumours are more likely to metastasize after the development of resistance to EGFR‐TKIs. CD146 is a multifunctional molecule and is implicated in tumour invasion and metastasis; however, its role in lung cancer has not been clearly established. Objective: Here, we aimed to explore the relationship between CD146 pathway and stem cell phenotype after EGFR‐TKI resistance in lung cancer. Methods: EGFR‐TKI‐resistant cell lines were established by exposing parental cells to erlotinib/gefitinib. The CD146 level was measured by a western blot, RT‐PCR and immunocytochemistry fluorescent. Cell migration was examined by the transwell assay and the scratch assay. Stemness phenotype genes were evaluated by RT‐PCR and stem cell phenotype was observed by the microsphere formation assay. Results: CD146 and stemness phenotype genes increased while β‐catenin decreased in acquired EGFR‐TKI‐resistant cell lines. CD146's over‐expression induced the up‐regulation of stemness‐related genes and was inversely correlated with the β‐catenin expression, which further increased the migration capability of resistant cancer cells. CD146's knockdown suppressed cell migration and stemness phenotype. Conclusions: CD146 molecule contributes to the stemness phenotype and migration in EGFR‐TKI‐resistant cells. CD146 might be a potential therapeutic target for EGFR‐TKI‐resistant lung cancer or metastasis prevention.